Seasonal changes in water-soluble brown carbon (BrC) at Nanling background station in South China - Zhang, Bolong; Tang, Jiao; Geng, Xiaofei; Mo, Yangzhi; Zhao, Shizhen; Zhong, Guangcai; Li, Jun; Zhang, Gan (Frontiers in Environmental Science, 2024)
Brown carbon (BrC) is an important light-absorbing component of organic carbon (OC), causing large uncertainty in aerosol radiative forcing evaluation and being related to health issues as well. Knowledge of BrC in an atmospheric background station is beneficial to understand its role in a changing climate. A year-long sampling campaign was conducted at Nanling background station to get a comprehensive knowledge of WS-BrC, a total of seventy-two PM2.5 samples throughout a year were used. Light absorption and fluorescence spectra of WSOC were analyzed synchronously using a fluorescence spectrophotometer. The low levels of PM2.5, OC, and elemental carbon (EC) conferred a background site. The optical properties of WS-BrC were characterized using excitation-emission matrix (EEM) fluorescence spectroscopy. The WS-BrC made a significant contribution (365 nm, 18% ± 10%) to total carbonaceous aerosol absorption. The mass absorption efficiency (MAE) of WS-BrC is 0.81 ± 0.34 m2 gC–1, and varies among seasons due to the different sources or atmospheric processing. Three EEM fluorescent components were identified by parallel factor (PAFAFAC) analysis, including two humic-like substances (HULIS, C1, C2), and one phenolic-like component. The HULIS components accounted for approximately 70% of the total fluorescence intensities. Primary combustion emissions showed enhanced activity during the winter and spring seasons, but there were no significant influences on WS-BrC in spring. Secondary sources contributed significantly to WS-BrC during winter, summer, and autumn (all exceeding 50%), except for spring. Photooxidation is a significant process in the formation of secondary WS-BrC in winter and autumn, but there may be another formation pathway in summer, i.e., the ammonia pathway. This study contributes to our understanding of BrC in the background atmosphere.